ANALISIS SERAPAN TENAGA KERJA DAN PENDAPATAN PETANI KELAPA SAWIT DI KABUPATEN PELALAWAN - IRSYADI SIRADJUDDIN (Jurnal Agroteknologi, 2016)
This research aims to know (1) characteristics of farmers oil palm; (2)  analysis of labour absorption; and (3) analysis of oil palm production; and (4) analysis of farmers income. The research was conducted in August 2015 until November 2015. Location of research in sub-districts of Bandar Seikijang, Langgam, Pangkalan Kuras, and Ukui in Pelalawan District. The method used interviews, questionnaires, and documentation. Sampling was done by purposive. The results showed (1) Characteristics of age of farmers are productive. While the characteristics of farmer education including secondary level (high school); (2) The most of labor absorption in sub-district Ukui (4,04 HOK / ha), followed by Bandar Seikijang (3,85 HOK / Ha), Pangkalan Kuras (3,80 HOK / ha), and Langgam (3,56 HOK /Ha); and (3) The highest productivity of oil palm in District Ukui (20,80 ton/ha), followed by Pangkalan Kuras (19,02 ton/ha), Bandar Seikijang (17,21 ton/ha), and Langgam (15,44 ton/ha). (4) The biggest income of farmers in District Ukui (Rp 23.750.347, - /ha), followed by Pangkalan Kuras (Rp 22.193.508, - /ha), Bandar Seikijang (19.100.916,- / ha), and Langgam (Rp 14.099.540, - / ha).